Gunfight at Rio bravo [videorecording (DVD)] - Cornet, Joe; Nevsky, Alexander, 1971-; Gruner, Olivier, 1960- (Shout! Factory, 2023)
When mysterious Russian gunslinger Ivan Turchin rides into a small East Texas town, he runs afoul of a bloodthirsty outlaw gang known as The Hellhounds. Outmanned and outgunned, the town must put their trust in Turchin to protect them from annihilation at the hands of the bandits. The gunslinger finds allies in the form of Marshal Austin Carter and Sheriff Vernon Kelly, and together the three must make a desperate stand against impossible and violent odds.